5 - Barriers to Middle-level Academic Leadership for Female Academics in Nigerian Higher Education - Omotoso, Sharon Adetutu (Journal of Higher Education in Africa, 2022)
With a rising number of women in middle-level higher education leadership, vast opportunities abound. Yet middle-level female academics are faced with sticky floors that jeopardise their significant inflow to senior leadership positions. By arguing that intra-feminist issues pertaining to higher education leadership’s leaky pipeline have not gained sufficient attention, this study interrogates internal dynamics among middle-level female academics, to identify threats to the prevalent notion of universal sisterhood that ought to boost women’s efforts at countering forces that militate against their upward movement in higher education (HE) leadership. This ethnographic work will engage with the literature, trends and narratives that are shaping women’s leadership in HE in West Africa, specifically among middle-level female academics in Nigeria’s public and private universities. Responding to the question of place-making for women in higher education leadership – at whose expense and to what end? – the study submits that beyond acclaimed androcentric barriers to women’s participation and representation in senior higher education leadership, there are less visible contributory factors among womenfolk, which lead to role entrapment and spatial entrapment. The study proposes symbiotic interactionism for female academics to attain and remain in the upper echelons of HE leadership.